Claudia Andujar: geografias do corpo - Mariana Dobbert Tidei (2019)
This research comprehends the necessity to enlarge the cartographic imagination, considering the geographic imaginaries that constitute the hegemonic narrative. In view of a world crisis, how to enlarge imaginative possibilities to other possible worlds? With this aim, we seek to understand the relationships that are established between lived world and imaginary(s) world(s), space and imagination, narrative and cartography, taking into account a critical displacement of the concept of cartography. The research explores the trajectory of the photographer and indigenous activist Claudia Andujar as a field of discussion, as we observe in her singular practice countermovements to the political-mediatic construction of a modern nation image, which took place in the 1970s in Brazil. We propose to understand Claudia Andujar as a geographic body, since the photographer was constantly moving between different worlds. Therefore, we intend to discuss her images in dialogue with the imaginaries that constituted the territory. In this way, her photos are explored here as cartographic dispositive, in view of the aesthetic-political practice of the photographer.